L-carnitine ameliorates oxidative damage due to chronic renal failure in rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Chronic renal failure (CRF) is associated with oxidative stress that promotes production of reactive oxygen species. L-Carnitine is a cofactor required for transport of long-chain fatty acids into the mitochondrial matrix. Recent research has shown that some clinical conditions (ie, anorexia, chronic fatigue, coronary heart disease, diphtheria, hypoglycemia, and male infertility) benefit from exogenous supplementation of L-carnitine. The aim of this study was to examine the role of L-carnitine in protecting the aorta, heart, corpus cavernosum, and kidney tissues against oxidative damage in a rat model of CRF. Male Wistar albino rats were randomly assigned to either the CRF group or the sham-operated control group, which had received saline or L-carnitine (500 mg/kg, i.p.) for 4 weeks. CRF was evaluated by BUN and serum creatinine measurements. Aorta and corporeal tissues were used for contractility studies or stored along with heart and kidney tissues for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels. Plasma MDA, GSH levels and erythrocyte superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities were also studied. In the CRF group, the contraction and the relaxation of aorta and corpus cavernosum samples decreased significantly compared with controls and were partially reversed by L-carnitine treatment. In the CRF group, there were significant increases in tissue MDA with marked reductions in GSH levels in all tissues and plasma compared with controls. In the plasma SOD, CAT and GSH-Px activities were also reduced. All these effects were reversed by L-carnitine as well. The increase in MDA level and the concomitant decrease in GSH level of tissues and plasma and also suppression of the antioxidant enzyme activities in plasma demonstrate that oxidative mechanisms are involved in CRF-induced tissue damage. L-carnitine, possibly via its free radical scavenging and antioxidant properties, ameliorates oxidative organ injury and CRF-induced dysfunction of the aorta and corpus cavernosum. These results suggest that L-camitine supplementation may have some benefit in CRF patients.
Keywords: chronic renal failure; reactive oxygen species; L-carnitine; rat; ERYTHROCYTE GLUTATHIONE-PEROXIDASE; ERECTILE DYSFUNCTION; SUPEROXIDE-DISMUTASE; LIPID-PEROXIDATION; OXYGEN RADICALS; KIDNEY-DISEASE; HEART-FAILURE; SMOOTH-MUSCLE; NITRIC-OXIDE; STRESS